2018
DOI: 10.1177/0192623318778508
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone in Combination with α-glycosyl Isoquercitrin Prevents Steatosis-related Early Hepatocarcinogenesis in Rats through the Observed NADPH Oxidase Modulation

Abstract: Administration of the diuretic, spironolactone (SR), can inhibit chronic liver diseases. We determined the effects of SR alone or in combination with the antioxidant α-glycosyl isoquercitrin (AGIQ) on hyperlipidemia- and steatosis-related precancerous lesions in high-fat diet (HFD)-fed rats subjected to a two-stage hepatocarcinogenesis model. Rats were fed with control basal diet or HFD, which was administered with SR alone or in combination with an antioxidant AGIQ in drinking water. An HFD increased body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Effects of the HFD on GST-P-positive preneoplastic liver foci were variable in our studies, probably reflecting variations due to the study condition and diet lot. Both the area and number of foci were significantly increased in the HDF group compared with the CTL group in our previous study (Murayama et al, 2018) or were both weakly increased without a significant difference in another study (Nakamura et al, 2018). The present study revealed only a minor effect on the number of GST-P-positive preneoplastic liver foci.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Effects of the HFD on GST-P-positive preneoplastic liver foci were variable in our studies, probably reflecting variations due to the study condition and diet lot. Both the area and number of foci were significantly increased in the HDF group compared with the CTL group in our previous study (Murayama et al, 2018) or were both weakly increased without a significant difference in another study (Nakamura et al, 2018). The present study revealed only a minor effect on the number of GST-P-positive preneoplastic liver foci.…”
Section: Discussionsupporting
confidence: 45%
“…Analysis of mRNA levels of the genes listed in Supplemental Table 2 in liver tissues (n = 6 animals per group) was performed with real-time reverse transcription-polymerase chain reaction (RT-PCR) as previously reported (Murayama et al, 2018). The relative differences in gene expression were calculated using the threshold cycle (CT) values that were first normalized to those of the hypoxanthine phosphoribosyl transferase 1 (Hprt1) gene, the endogenous control in the same sample, and then relative to a control CT value using the 2−ΔΔCT method (Livak and Schmittgen, 2001).…”
Section: Real-time Reverse Transcription-polymerase Chain Reaction Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Its expression seems to affect cancer progression and metastasis, being implicated in the modulation of KRAS–RAF oncogenic signaling [ 54 ]. Yoshida et al observed that the NOX subunit p22phox is expressed in preneoplastic hepatic foci during HFD-induced hepatocarcinogenesis, and the mineralocorticoid spironolactone in combination with β-glycosyl isoquercitrin is able to prevent these steatosis-induced precancerous lesions by reducing p67phox expression and the number of p22phox-positive cells [ 73 ].…”
Section: Noxs and The Nash–hcc Transitionmentioning
confidence: 99%